Broad organ acceptance and equitable access to early kidney transplantation. Issue 4 (28th January 2023) - Zaphiros, Nikolas H.; Nie, Jing; Chang, Shirley; Shah, Vaqar; Kareem, Samer; Zaaroura, Ahmad; Kayler, Liise K.
Abstract: Background: Broad organ acceptance can increase early kidney transplantation (KTX) within <1‐year of dialysis initiation while improving access inequity. Methods: Single‐center data of adult isolated deceased‐donor KTX recipients between 2013 and 2020 were stratified into three 2.5‐year periods before‐, early after‐, and late after our center's deceased‐donor organ acceptance practice change, excluding a 6‐month implementation period. Outcomes were assessed within five recipient subgroups based on demographic and clinical characteristics. Results: Of 704 recipients, the frequency of early KTX was 22% pre‐change, 36% early post‐change, and 34% late post‐change. Given similar post‐change frequencies of early KTX, post‐change eras were combined to improve analytic power of subgroup analyses. After the organ acceptance practice change (vs. pre‐change), the likelihood of early KTX increased variably within historically underserved groups, including recipients who were older (37%–39%, p  = .859), Black (10%–21%, p  = .136), female (21%–37%, p  = .034), diabetic (13%–32%, p  = .010), and BMI≥35 kg/m 2 (20%–34%, p  = .007). Despite the practice change, Black recipients continued to experience less early KTX compared to non‐Black recipients. The likelihood of delayed graft function was significantly increased ( p  < .001), and 1‐year creatinine was significantly higher ( p  < .001) post‐practice change, but between‐era risk‐adjusted death‐censored graft survival was similar. Conclusions: Transition to broader donor acceptance was associated with more early KTXs among historically underserved patient subgroups. However, the effect was non‐significant among Black recipients, suggesting the need for additional strategies to impact early transplant access for this population. Studies of broad organ acceptance are needed to examine both access and outcomes.